Chairperson collectivism and the compensation gap between managers and employees: Evidence from China. (25th March 2019) - Jiang, Wei; Lin, Bingxuan; Liu, Yunguo; Xu, Yue
Abstract: Research Question/Issue: Few studies have examined the determinants of the compensation gap between managers and workers, despite the significant public attention the issue has received. In particular, few studies have examined how nations' formal systems, such as their institutional and legal arrangements, and informal systems, such as their cultures and traditions, affect the compensation gap. We use the chairperson's native place of origin as a proxy for cultural differences within China and examine how chairperson collectivism affects compensation gaps between managers and average workers. Research Findings/Insights: The results show that the compensation gap in a company run by a chairperson from a collectivistic culture tends to be smaller than that of a company run by a chairperson from an individualistic culture. This effect tends to be stronger if a chairperson has a longer tenure and works in a state‐owned enterprise or in a firm located in collectivistic regions. Theoretical/Academic Implications: The study provides new insights into the determinants of the compensation gap by incorporating the cultural traits of management. It also broadens the understanding of compensation gaps in emerging markets and shows that cultural differences play an important role in understanding the compensation gap in China. Practitioner/Policy Implications: Cultural characteristics should be taken into account when developing compensation contracts. Stakeholders need to consider alternative mechanisms, such as higher pay for performance, to counteract the higher compensation gap due to differences in cultural preferences.